2014
DOI: 10.1016/j.addbeh.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Substance use over the military–veteran life course: An analysis of a sample of OEF/OIF veterans returning to low-income predominately minority communities

Abstract: This paper presents an overview of substance use patterns of recent veterans returning to low-income predominately minority communities over four periods of the military-veteran career. Respondent driven sampling (RDS) was used so that unbiased estimates could be obtained for the characteristics of the target population. The majority of participants had used marijuana but no other illegal drugs. In the military, marijuana use was substantially lower and alcohol was the drug of choice; the majority were binge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…29 Limited evidence suggests that leaving the military is associated with an increased likelihood of cigarette smoking, marijuana use, and nonmedical use of prescription painkillers among OEF/OIF veterans. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Limited evidence suggests that leaving the military is associated with an increased likelihood of cigarette smoking, marijuana use, and nonmedical use of prescription painkillers among OEF/OIF veterans. 14 …”
Section: Discussionmentioning
confidence: 99%
“…In a small sample of OEF/OIF veterans, their cigarette smoking, marijuana use, and nonmedical use of prescription painkillers was more prevalent after leaving the military. 14 Further, approximately 11% of OEF/OIF veterans seeking care in the Veterans Health Administration have a substance use disorder diagnosis. 15 Additionally, substance use among veterans is associated with homelessness 16 and suicide.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown how geographic location or connection to military bases influence these findings, and future research could explore the relationship of locations of home communities or military bases with regulations regarding marijuana access and legal consequences in those communities. 24 …”
Section: Discussionmentioning
confidence: 99%
“…14 One study found that 33.7% of OEF/OIF veterans in low-income, predominantly minority neighborhoods within New York City reported using marijuana in the past 30 days. 24 Our inclusion of variables that control for time trends (FY of deployment), the number of specimens tested and observation months is a particular strength of this study. Drug testing frequency varies among members and follow-up windows were not uniform in length (e.g., members returning from deployments in FYs 2010 and 20111 had shorter follow-up windows and fewer chances to get tested), thus controlling for these variables strengthens the validity of our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rates of amphetamine and narcotic prescription use are increasing among active duty members (Bray et al, 2010) and veterans (Wagner et al, 2007). Moreover, in a study of substance use over the military-veteran life course, Golub and Bennett (2014) found marijuana use and prescription pain killer misuse increased after separation from military service.…”
Section: Introductionmentioning
confidence: 95%